Levels of Mercury in Persian Gulf Frozen Fish Species - Parisa Ziarati; Fatemehsadat Mirmohammad Makki (Islamic Azad University, 2017)
Severe discharge of sewage and industrial effluents into the Persian Gulf leads to the deposition of various types of heavy metals, especially lead and mercury, in the muscles of fish. Total mercury and methylmercury contents were determined in the edible parts (muscle tissue, fillet) of two different most popular frozen fish species from the Persian Gulf to ascertain whether the concentrations exceeded the maximum level fixed by the European Commission or not. During the period from October 2015 to June 2016, a total of 150 frozen fish packaged samples were randomly collected from the recognized supermarkets in Tehran province, Iran. The mercury (Hg) concentration of samples was determined by atomic absorption spectrophotometer using a mercuric hydride system (MHS 10) and also by direct mercury analyzer (DMA). High concentration of total Hg was found in a Carcharhinus dussumie brand (0.91 ± 0.12 μg/g) while the lowest level was detected in Pomadasys furcatus (0.29 ± 0.02 μg/g). In current study the mean concentrations of Mercury in all studied frozen fish samples were 0.79 ± 0.11 µg/g that means Hg levels were above 0.5 μg/g, which is the maximum standard level recommended by Joint FAO/WHO/Expert Committee on Food Additives (JECFA). In 13% of Pomadasys and in 47.2 % of Carcharhinus fish samples total mercury concentrations exceeded the maximum level fixed by the European Commission. All samples had also mean Hg concentrations that exceeded EPA's established safety level of 0.3 μg/g.